A DPA-based highly selective and sensitive fluorescent probe for mercuric ions and its imaging in living cells. Issue 23 (25th May 2016) - Jia, Junhua; Wu, Luling; Ding, Yu; Huang, Chusen; Zhu, Weiping; Xu, Yufang; Qian, Xuhong
Abstract : A DPA-based fluorescent probe was designed and synthesized for the recognition of mercuric ions and imaging in living cells. The fluorescent probe exhibits excellent selectivity and sensitivity toward Hg 2+, and the detection limit was calculated to be 5.49 nM. Abstract : Based on the 2, 2-dipicolylamine (DPA) receptor and naphthalimide fluorophore, three fluorescent probes, RDPA, MDPA andVDPA have been developed for the recognition of mercuric ions. Among them, VDPA, bearing a diglycol group in the imine chain, exhibits good water solubility, and high selectivity towards mercuric ions in PBS water solution. With DPA as the receptor, VDPA showed very high affinity and sensitivity towards Hg 2+, and the binding constant and detection limit were calculated to be 2.8 × 10 10 M −1 and 5.49 nM, respectively. The MTT assay and living cell imaging experiments suggested that the probeVDPA has potential application for detecting Hg 2+ in living cells.